The Role of Shadow Teachers (GPK) in Optimizing Pull-Out Classes for Children with Special Needs in Inclusive Schools - Fauziyah, Ana Fatwa; Utami, Ratnasari Diah (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2023)
Children with special needs (ABK) are children who must receive special treatment, not least in terms of education. Children with special needs have the same right to education. To facilitate educational needs, inclusive schools were created; one of the schools that facilitate this in the Kartasura sub-district is MI Muhammadiyah PK Kartasura, where in its implementation, there is one special teacher who accompanies it, called a shadow teacher. The problem that exists in this inclusive school is that the pull-out class learning needs to be optimized, and the use of available learning media resources needs to be optimized. This research aims to find out 1) the characteristics of children with special needs, 2) the role of shadow teachers for children with special needs, and 3) the optimization strategy used by the pull-out class for children with special needs at MIM PK Kartasura. The method used in this paper is a qualitative descriptive review. Data were collected using observation, interview, and documentation techniques. This research is a case study research that analyzes the subjects and objects that exist more deeply and then concludes. This research uses a data validity test and a data analysis test. The results showed that 1) there are 12 categories of children with disabilities in MIM PK Kartasura, 2) the role of the shadow teacher in the pull-out class has been running well thanks to the cooperation between the shadow teacher and the children with disabilities, 3) the strategy applied to optimize the pull-out class by using a differentiation approach, the shadow teacher monitors the child's progress regularly to find out the child's development, and is supported by providing continuous training to the shadow teacher.